Penerapan Program Software Matlab Dalam Memecahkan Permasalahan Rangkaian Listrik: Dinamika Sistem Kapasitor Dan Induktor (Prinsip Nilai Dan Vektor Eigen) - Muthoharoh, Luluk; Pamungkas, Muhammad Putra; Sari, Reni Permata (Jurnal Fisika Unand, 2021)
Matlab software was applied in solving physics cases in electronics using value calculation programs and Eigenvectors. The physics case solved is an moving oscillator circuit consisting of five capacitors and four inductors. The purpose of this program is to determine the value and the Eigenvectors that can be obtained. The method used is to utilize the problem of values and Eigenvectors in the Matlab program. In the case of oscillator motion, each capacitor's size and inductor system have been determined according to the system.. The equation of motion for the capacitor and inductor system is reviewed at each point of the inductor and the function used is Â called the ansatz function, then differentiated twice concerning time. By using the Matlab program application, the results obtained show that by using eig (Eigen) command the Matlab program can accurately show the results of running (execution) values and Eigenvector.